Development Media Learning Geography with Applications Kahoot! as Media Evaluation Results Study Students in SHS 10 Padang - Iswara, Dedi; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2023)
Learning media is one of the supporting components of learning. Learning media has the benefit of increasing student interest and creativity, besides that learning media also influences student learning interest. The media used should follow current developments in science and technology. The media also helps in evaluating student learning outcomes. The purpose of this study is to describe the feasibility, effectiveness, and student responses regarding the use of Kahoot! in learning activities as a medium for evaluating learning outcomes. The development model used by researchers, namely the 4D model, is formed from 4 main stages such as: define, design, develop, and disperse. The results of validation by material experts obtained a proportion of 84% "valid". Media experts get a proportion of 87% "valid". Furthermore, the test results obtained an average pre-test score of 42.89 students and a Post-test of 87.4, there was an increase in value of 44.51. The last student's response to the use of Kahoot obtained the proportion of 92% "very good". So it can be concluded that the song Kahoot! that researchers developed is relevant and interesting to serve as a medium for evaluating student learning outcomes.